Adolescent empowerment programmes in two vulnerable populations: a cross-cultural study in rural Australia and rural India - Mohajer, Nicole (Curtin University, 2009)
Poor adolescents who are not attending school are a low priority in the minds and budgets of the people of the world. They are understudied, highly at risk for poor health outcomes and are less likely to be able to access health services, health promotion activities and other programmes designed to improve the well-being of the poor and needy. This thesis reports on a cross-cultural qualitative study with two populations: Aboriginal Australian adolescents who were poor attendees at school and rural North Indian adolescents who were school dropouts (or never enrolled). Both populations were further disadvantaged by belonging to socially disadvantaged and oppressed communities. The aim of the research was to identify the role of empowerment in improving the health and well-being of disadvantaged populations who are socially marginalised using the empowerment pedagogy of Freire.The settings for the research were rural areas with high levels of youth illiteracy, unemployment, substance abuse and ill-health. The Indian site was in the state of Uttar Pradesh, and was conducted in three districts of the state in sites that covered a wide range of social, religious and economic backgrounds. Most of the participants were from the lowest socio-economic strata of society and had left school because of poverty, inaccessibility of school or family pressure. The Australian site was deidentified at the request of the participants and included two Aboriginal-controlled communities and a large rural town with a high population of Aboriginal residents. Participants were poor attendees at school because of social disruption, poor academic performance, perceived discrimination or disinterest.Using an empowerment model developed during the literature search, elements of the empowerment process were tested in sequential focus group discussions and indepth interviews with out-of-school adolescents in both countries using a standard questionnaire developed in consultation with participants in the first pilot project. Data was analysed for each site and merged and compared across sites in each country and between each country until there were clear themes that emerged. The findings identified the identified needs of participants, the usefulness of the empowerment process and positive and negative features of the methodological approaches of empowerment; particularly peer education and the development of awareness through problem posing or critical discussion of photos and pictures.Despite the challenges involved in engaging ‘disempowered’ or ‘oppressed’ populations, this research provided an insight into the feasibility of empowerment programmes for health promotion and social change with vulnerable adolescents. Furthermore the study offered an opportunity to document the ‘generalisability’ of empowerment materials, methods and strategies to adolescents in diverse cultural and social situations.The findings support the promotion of empowerment methods as a means of health promotion and identification of the needs of vulnerable adolescents. In addition it highlighted the importance of making a commitment to also address the social determinants of health (education, sanitation, social justice and infrastructure) in communities and to involve parents and authority figures in the empowerment process. The special role that culture, traditions, families and the desire to learn play in the lives of vulnerable adolescents was revealed through the in-depth interviews and focus group discussions that were the mainstay of the research method. Recommendations for health promotion on a variety of levels are given, along with a proposal for a model of empowerment and suggestions for further research.